(untitled) (Revista horizonte, 2014)
Objective: To identify the employment situation of the graduates of the Pedagogy in Secondary Education course in Physical Education of the Universidad de Los Lagos, Campus Osorno. Methods: 51 graduates of both sexes (34 males and 17 females) were surveyed. The survey presents 45 questions, divided into 3 dimensions. The first refers to Personal Identification and consists of 12 questions, the second refers to the graduate’s Work Activity with 17 questions and the third refers to the Evaluation of Training and has 16 questions. Data analysis was carried out using SPSS 18.0 Statistical Analysis Software (Stastistical Pack for Social Sciences). Results and conclusions: The results obtained indicate that the vast majority of the graduates are working in the different areas of specialization offered by the discipline such as: Middle and Elementary Education, Physical Trainers (gymnasiums), and Recreation. The great majority of the graduates feel satisfied with the training they received, which is an excellent indicator to continue improving the quality of the training.